CHYDENANTHUS MIERS (LECYTHIDACEAE) - Kuswata Kartawinata (Research Center for Biology, 1982)
Chydenanthus is accepted as a monotypic genus and its type species C. excelsus (Bl.) Miers is redescribed. C. dentato-serratus R. Knuth belongs to Barringtonia and is thus excluded from the genus.